Associations of metabolic dysfunction-associated fatty liver disease and hepatic fibrosis with bone mineral density and risk of osteopenia/osteoporosis in T2DM patients - Zhang, Wei; Li, Yuhua; Li, Shangjian; Zhou, Jingqi; Wang, Kai; Li, Zhibin; Chen, Ning; Chen, Xueqin (Frontiers in Endocrinology, 2023)
Background Existing evidence on the associations of liver steatosis and fibrosis with bone mineral density (BMD) and risk of osteopenia/osteoporosis was limited with conflicting results. We aimed to evaluate the associations of metabolic dysfunction-associated fatty liver disease (MAFLD) and hepatic fibrosis with BMD and risk of osteopenia/osteoporosis in type 2 diabetes mellitus (T2DM) patients. Methods Baseline information of an ongoing cohort of 249 T2DM patients in Xiamen, China was analyzed. MAFLD was defined as the presence of hepatic steatosis [diagnosed by either hepatic ultrasonography scanning or fatty liver index (FLI) score >60] for T2DM patients. BMD was measured using dual-energy x-ray absorptiometry at total lumbar (L2–4), femur neck (FN), and total hip (TH) and was categorized as normal (T ≥ −1.0), osteopenia (−2.5 < T < −1.0), or osteoporosis (T ≤ −2.5) according to its minimum T-score. Results Among the 249 T2DM patients, prevalence rates of MAFLD, osteopenia, and osteoporosis were 57.8%, 50.6%, and 17.7%, respectively. Patients with MAFLD had significantly higher BMD T-scores of L2–4, FN, and TH and the minimum as well as lower prevalence of osteoporosis than patients without MAFLD. Hepatic steatosis indices, including FLI score, fatty liver (FLI ≥ 60 or hepatic ultrasonography scanning), and MAFLD, were significantly and positively associated with all T-scores, while hepatic fibrosis index and FIB-4 score, but not NAFLD fibrosis score (NFS), were negatively associated with all T-scores. MAFLD was significantly associated with the decreased risk of osteopenia/osteoporosis and osteoporosis with unadjusted odds ratios (ORs) (95% CI) of 0.565 (0.324–0.987) and 0.434 (0.224–0.843) (both p-values < 0.05), respectively. As for liver fibrosis, FIB-4 score, but not NFS, was significantly associated with elevated risk of osteoporosis with an unadjusted OR (95% CI) per SD increase of FIB-4 score of 1.446 (1.080–1.936, p-value = 0.013). Adjusting for potential confounding variables, especially body mass index, in the multivariable regression analyses, all associations of hepatic steatosis and fibrosis indices with BMD and risk of osteopenia/osteoporosis were not statistically significant. Conclusion MAFLD and hepatic fibrosis were not significantly associated with BMD and risk of osteopenia/osteoporosis independent of obesity. Nevertheless, screening and management of MAFLD and osteopenia/osteoporosis were still important for the prevention of fracture in T2DM patients.